A Theoretical Evaluation of Community Participation in Nyanguku Ward Dam Construction Project in Geita, Tanzania - Kiula P. Kiula; Walter Timo de Vries; Jenipher Kalori (Sekolah Tinggi Pertanahan Nasional, 2026)
Land use planning projects in Tanzania face low participation. Currently we do not know why this is so or under which conditions participation could be high or low. Hence, the research objective is to unveil why or under which conditions participation can be high or low. We use two theoretical perspectives on participation to test this: 1) public good theory stating that participation is low if the project concerns a public good. 2. Participation motivation theory (3 types), stating that-people participate based on their transaction benefits. The test case concerns a dam construction funded by the Tanzania Social Action Fund III. Communities are assumed to participate in making decisions throughout the project. We used questionnaires to unveil how and when people participated. The findings reflect the claims of public good theory in a very few aspects. However, social exchange theory, one of the motivational theories seems to reflect participation behavior the best. We recommend further research to investigate factors for amplifying social exchange theory to enhance participation in land use projects in developing countries.